Molecular characterization and expression analysis of hsp60 gene homologue of sheep blowfly, Lucilia cuprina. (August 2015) - Kumar Singh, Manish; Janardhan Reddy, P.V.; Sreedhar, A.S.; Tiwari, P.K.
Abstract: The 60 kDa heat shock protein (Hsp60) or chaperonin is one among the highly conserved families of heat shock proteins, known to be involved in variety of cellular activities, including protein folding, thermal protection, etc. In this study we sequence characterized hsp60 gene homologue of Lucilia cuprina, isolated and cloned from the genomic library as well as by genomic PCR, followed by RACE- PCR. The L. cuprina hsp60 gene/protein expression pattern was analyzed in various tissues, either at normal temperature (25±1 °C) or after exposure to heat stress (42 °C). The analysis of nucleotide sequence of Lchsp60 gene revealed absence of intron and the nuclear localizing signal (NLS). The deduced amino acid sequence showed presence of unique conserved sequences, such as those for mitochondrial localization, ATP binding, etc. Unlike Drosophila, Lucilia showed presence of only one isoform, i.e., hsp60A . Phylogenetic analysis of hsp60 gene homologues from different species revealed Lchsp60 to have >88.36% homology with D. melanogaster, 76.86% with L. sericata, 58.31% with mice, 57.99% with rat, and 57.72% with human. Expression analysis using Real Time PCR and fluorescence imaging showed significant enhancement in the expression level of Lchsp60 upon heat stress in a tissue specific manner, indicating its likely role in thermo-tolerance as well as in normal cellular activities.